Analisis Faktor-Faktor Penyebab Perceraian di Kabupaten Indramayu Tahun 2018: (Studi Kasus di Pengadilan Agama Indramayu Tahun 2018) - Syaefullah; Nurmahmudah (MAHAKIM Journal of Islamic Family Law, 2018)
The divorce case in the Indramayu Regency Religious Court in 2018 the divorce rate is still high, the factors that cause divorce in the Indramayu Religious Court in 2018 are economic factors of 5296 cases, leaving one party 56 cases, sentenced to 36 cases, ongoing disputes 25 cases, 5 cases of gambling, 2 cases of polygamy, 2 cases of disability, domestic violence 2 Case, forced marriage of 2 cases and apostasy of 1 case. The results of the analysis of economic factors are the main causes of divorce because many husbands do not provide for their wives and children, resulting in ongoing disputes and arguments in the household. So that many wives decided to sue her husband for 5170 people, and after divorce decided to go abroad to become migrant workers.Based on data from the BP2TKI LTS in 2018 the workforce from Indramayu is still dominated by female workers totaling 13,480 people, a factor causing divorce in Indramayu also because the education level of divorce actors is still low based on statistical data from the Indramayu Religious Court in 2018 of 3296 plaintiffs / the majority of applicants were educated only to the level of elementary school graduated